Implementasi Kepatuhan Syariah dalam Perbankan Islam (Syariah) (Studi Perbandingan antara Malaysia dan Indonesia) - Agus Triyanta (Fakultas Hukum Universitas Islam Indonesia, 2009)
Since the compliance towards shari’ah principles is mandatory in Islamic banking, the shari’ah advisory and supervision is another important aspect. It is also said that the shari’ah advisory and supervision is part and parcel of shari’ah compliance. In this regard, the regulation on shari’ah advisory or supervision, which also covers the role of shari’ah board, shall occupy the central part within the shari’ah compliance regulatory framework. In light of the abovementioned reasons, the research and discussion on shari’ah compliance, together with the role of the shari’ah board is very demanding and relevant to the current problems in the Islamic banking business. This paper will focus on the regulatory framework of the shari’ah compliance and its implementation in Islamic banking in Malaysia and Indonesia. Through the comparison between the two countries, some advantages will be identified.Particular reference should be made to the regulations and their implementation in the Islamic banking in Malaysia and Indonesia since there are few valuable considerations. Malaysia experienced the advanced development of Islamic banking compared to the rest of the Asian Muslim countries in the Southeast Asia region. The both countries are moslem dominated countries, and also, they share in the affiliation to Shafi’i Madhhab.Key word: compliance shari’ah, the Islamic banking